From source to sip: assessing contamination, health risks, and strategies for safe drinking water - Shree Alagesan, Lekha; Kundapur, Shruddha; Ravali, Annaram; Kumar Doddaiah, Sunil (International Journal Of Community Medicine And Public Health, 2025)
Safe drinking water is vital for public health, especially in communal settings like educational institutions. This study examines the journey of drinking water “from source to sip,” assessing potential contamination, associated health risks, and interventions to ensure water safety. At the institutional level, water sample collection typically involves identifying multiple critical points in the water supply system, including source water (e.g., borewells, municipal supply tanks), storage tanks (overhead and underground), distribution points (e.g., water coolers, taps, filters, dispensers in classrooms, hostels, and kitchens), end-use outlets (points where students or staff actually consume water). Samples are collected following sterile procedures and tested for physical, chemical, and microbiological parameters such as pH, turbidity, residual chlorine, heavy metals, and indicators of faecal contamination (like E. coli). Findings from such institutional studies often reveal contamination risks from aging pipelines, poorly maintained tanks, or inadequate treatment processes, potentially leading to waterborne illnesses. This research emphasizes regular monitoring, timely maintenance of water infrastructure, awareness among staff and students, and adopting advanced purification technologies as crucial strategies to ensure safe drinking water in educational environments.